Co-activator p120 is increased by gonadotropins in the rat ovary and enhances progesterone receptor activity - Ogata-Kawata Hiroko; Yazawa Takashi; Yamada Kazuya; Mizutani Tetsuya; Yoshino Miki; Sekiguchi Toshio; Kajitani Takashi; Miyamoto Kaoru (BMC, 2006)
Abstract Background Ovarian follicular development is primarily dependent on pituitary gonadotropins. Identification of gonadotropin-inducible genes in the ovary is one of the effective approaches for the study of follicular development. In this study we identify rat homologue of p120, a nuclear transcription co-activator, as one of the FSH inducible genes in the rat granulosa cells. Methods A full-length cDNA encoding rat p120 was cloned, and expression of the gene in the ovary was examined by Northern blotting. Tissue localization of p120 was examined by in situ hybridization. Cellular functions of p120 were studied by co-transfection of rat p120 gene together with estrogen receptor (ER)-alpha, ER-beta, androgen receptor (AR), or progesterone receptor (PR) genes. Results A full-length cDNA encoding rat p120 was characterized as a protein with 957 amino acid residues. Rat p120 was expressed ubiquitously, but strongly in the ovary and the testis. Expression of p120 mRNA was also induced in vivo by PMSG or PMSG/hCG treatment. Strong expression of p120 mRNA was observed in the granulosa cells of pre-ovulatory large antral follicles. Progesterone receptor was co-localized with p120 in the large antral follicles. Co-transfection experiments revealed that rat p120 activated AR, ER-alpha, ER-beta, and PR in the presence of their respective ligands. Conclusion These observations suggest that rat p120 is strongly induced in the ovarian granulosa cells, and may work together with PR in the granulosa cells of ovulatory follicles to promote the ovulation process.